POSHAN’s abstract digest on maternal and child nutrition research – Issue 17 - Avula, Rasmi (International Food Policy Research Institute, 2017)
This issue of the Abstract Digest features several papers of interest to nutrition in India, including a set of papers on determinants of nutritional outcomes and trends, a set of papers on narrative and empirical analyses of change in nutrition and a summary of findings on lipid-based nutrient supplements. It also features IFPRI’s 2017 Global Food Policy Report which looks at the impact of rapid urban growth on food security and nutrition, the 2016 India Spotlight Index from the Access to Nutrition Index, that evaluates the performance of the largest national food and beverage manufacturers’ policies, practices and disclosure related to nutrition in India, and a new UNICEF (2017) report on the implications of the 2030 Agenda for children and the data required to monitor the situation of children within the SDG framework.